11.41: Numerical investigation of influence of plate yield point on performance of steel plate shear wall. (13th September 2017) - Moammer, Omid; Deylami, Ardeshir.; Jafari, Khashayar; Raisszadeh, Amir Hossein
ABSTRACT: Steel plate shear walls (SPSW) consist of thin infill steel plates attached to beams and columns in steel frames. SPSW are efficient lateral load resisting systems and can act as an alternative to traditional systems. In this study, the nonlinear response of single‐story single‐bay SPSW models having different yield points of infill plates (100, 180, 250 MPa.), were numerically investigated under lateral loading. The other variables in the analysis were the aspect ratio of panels (2 and 2.5), and thickness of the steel plates (3, 5 and 7 mm.). The models were designed according to the "AISC Steel Design Guide 20" and the "AISC 341–10 Provisions". Finite element models of SPSWs were developed and analysed using ABAQUS nonlinear program. The results show that, using low yield point steel leads to more ductility and with some consideration influence the stiffness of models.